Achievement motivation and self-efﬁcacy perception amongst portuguese pharmacy students - Cavaco, Afonso (2011)
Portuguese pharmacy education is undergoing a process of change and the present curriculum of the Lisbon Faculty of Pharmacy (FFUL) is under active discussion. Programs can be better developed to simultaneously achieve learning objectives and students’ success. Previous research has found students’ goal orientation to be consistent with their beliefs about how success is achieved. This work aimed at measuring dimensions of Achievement Motivation (Task Orientation, Ego Orientation and Work Avoidance) and Self-efﬁcacy Perception amongst a sample of 1st and 5th year Portuguese pharmacy students, including those from a private college (ISCS). Both scales, previously used for educational research in Portugal, conﬁrmed the three motivational dimensions and the self-efﬁcacy construct, through Principal Component Analysis and internal consistency testing. Preliminary analysis showed behavioural differences between ﬁrst and ﬁnal year students within FFUL and ISCS. These results suggest that a curriculum reform needs to entail not only the update of subject content but also the customisation of teaching and learning methods according to years of academic experience